1995
DOI: 10.1007/3-540-44750-4_33
|View full text |Cite
|
Sign up to set email alerts
|

t-Cheater Identifiable (k, n) Threshold Secret Sharing Schemes

Abstract: Abstract. In this paper, we show that there exists a &cheater identifiable (k, n) threshold secret sharing scheme such as follows for cheating probability e > 0. If k 2 31 + 1, then 1. Just k participants are enough to identify who are cheaters.2. 1x1 is independent of n. That is, 1x1 = lSl(l/e)(t+2), where S denotes the set of secrets and V, denotes the set of shares of a participant Pi, respectively.(Previously, no schemes were known which satisfy both requirements.)Further, we present a lower bound on lvtl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 10 publications
2
45
0
Order By: Relevance
“…While this condition is the same as that of Kurosawa et al [12], the share size is dramatically reduced compared to [12]. Namely, the share size of the first scheme satisfies |V i | = |S|/ and is only one bit longer than the bound of eq.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…While this condition is the same as that of Kurosawa et al [12], the share size is dramatically reduced compared to [12]. Namely, the share size of the first scheme satisfies |V i | = |S|/ and is only one bit longer than the bound of eq.…”
Section: Introductionmentioning
confidence: 82%
“…The size of share |V i | of their scheme is |V i | = |S| 3n−2 where |S| denotes the size of secret 1 . In [12], Kurosawa, Obana and Ogata showed that when the number of cheater t satisfies t ≤ (k − 1)/3 the share size is greatly reduced compared to that of [21]. The size of share of their scheme is |V i | = |S|/ t+2 , which until now has been the most efficient scheme, despite the fact that the bit length of their scheme is still linear to the number of cheaters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A framework for considering robust secret sharing is provided in [1], which includes schemes in both the information-theoretic and computationally secure settings. Secret-sharing schemes that either detect or identify participants who present incorrect shares during an attempted recovery have also been extensively studied, for example [17,21,22]. While such schemes make it apparent that cheating has occurred, they do not necessarily permit honest participants to recover the correct secret.…”
Section: Introductionmentioning
confidence: 99%
“…Secret sharing is a fundamental building block for many cryptographic protocols and is often used in the general composition of secure multiparty computations. In recent, secret sharing has still been an active research area because of its importance in cryptography [2][3][4][5][6][7][8][9][10][13][14].…”
Section: Introductionmentioning
confidence: 99%